1996
DOI: 10.1143/jjap.35.l741
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Multilayered Conducting Polymer Heterostructure by Self-Assembly Technique and Its Optical and Electrical Properties

Abstract: The formation of galaxies, clusters and superclusters (SCs) is discussed based on a cosmic string model, and the constrain& are given for the corresponding loops which form these structures by the accretion of the loops. Only those loops that came into horizon after teq (the time of equal matter and radiation) may be the seeds of clusters and SCs. &BComic s t r i n g s are one-dimensional t o p o l o g i c a l d e f e c t s formed i n cert a i n p r o c e s s of GUT(grand u n i f i e d t h e o r y ) d u r i n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…[156][157][158][159][160][161][162] As reported by Yoshino and coworkers in 1996, solutions of poly(3-a-carboxylmethylthiophene) (P32) (Scheme 9) at pH ¼ 4.5 and poly(dihexyldipropargyl ammonium bromide) (P33) (Scheme 9) were used to fabricate by a LBL processes an ITO/ P32:P33/Al device containing 11-13 bilayers. [21] This group similarly prepared devices with P32 and poly(N-methyl-2,5-pyridinium vinylene) (P34) (Scheme 9), [163][164][165] as well as REVIEW the same P32:P34 devices doped with C 60 or a porphyrin derivative by using a mixed solution of P32 with an adduct of fullerene and 8-(9-anthryl)-7-oxaoctanoic acid [163] or a mixed solution of P34 with a porphyrin derivative. [164] These LBL devices had enhanced photoconductivity and increased PL quenching over adsorbed single layer or spun-coated layers.…”
Section: Solar Cells and Photodetectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…[156][157][158][159][160][161][162] As reported by Yoshino and coworkers in 1996, solutions of poly(3-a-carboxylmethylthiophene) (P32) (Scheme 9) at pH ¼ 4.5 and poly(dihexyldipropargyl ammonium bromide) (P33) (Scheme 9) were used to fabricate by a LBL processes an ITO/ P32:P33/Al device containing 11-13 bilayers. [21] This group similarly prepared devices with P32 and poly(N-methyl-2,5-pyridinium vinylene) (P34) (Scheme 9), [163][164][165] as well as REVIEW the same P32:P34 devices doped with C 60 or a porphyrin derivative by using a mixed solution of P32 with an adduct of fullerene and 8-(9-anthryl)-7-oxaoctanoic acid [163] or a mixed solution of P34 with a porphyrin derivative. [164] These LBL devices had enhanced photoconductivity and increased PL quenching over adsorbed single layer or spun-coated layers.…”
Section: Solar Cells and Photodetectorsmentioning
confidence: 99%
“…Recent research on the application of CPEs in biological and chemical sensors [13][14][15][16] has led to a greater structural diversity and new synthetic protocols for their preparation. [17,18] Introduction of these new materials into optoelectronic devices has led to improvements relative to earlier work on CPEcontaining PLEDs, [19,20] photovoltaic devices [21] and polymer light-emitting electrochemical cells (PLECs) [22] fabricated by either single film deposition or layer-by-layer (LBL) deposition techniques. [23] There is a growing recognition that CPEs REVIEW…”
Section: Introductionmentioning
confidence: 99%
“…Negatively charged poly(3-carboxymethylthiophene) 33 has also been studied by Kawai et al in combination with a positively charged conducting polymer of structure 37 62) . It has been observed that photoluminescence from the positively charged conducting polymer is quenched markedly in the multilayered heterostructure system.…”
Section: Conducting-polymer Multilayersmentioning
confidence: 99%
“…Using other materials, such as conductive polymers [3][4][5], organic dyes [6], proteins, micelles, clays [7], and organic [8] or inorganic [9][10][11] particles, it is easy to fabricate hetero-structures. The electrical or optical properties [12] and energy transfer mechanism [13] have been reported. It can also be combined with other techniques [14], such as micro-printing [15,16] and the surface sol-gel method [17].…”
Section: Introductionmentioning
confidence: 99%